The effect of parotid gland examination and massage on serum amylase levels in patients with acute parotitis - Fatih Evcimik, Muhammed; Ömür Çakır, Burak; Adnan Cırık, Ahmet; Cevizci, Raşit; Soylu, Erkan; Günay, Celal (ENT Updates, 2016)
Objective: Acute infection of the parotid gland is common in the clinical practice of ear-nose-throat medicine. The present study aims to demonstrate the effect of parotid gland massage on serum amylase levels. Methods: The study included 30 patients with acute parotitis presenting to our clinic and 14 healthy volunteers. The correlation between the serum samples collected before and after parotid gland massage was compared. Results: A significant difference was observed in the amylase levels before and after massage in the acute parotitis group. Amylase levels did not differ significantly between measurements before and after massage in healthy subjects. Conclusion: Patients should be evaluated with consideration to the effect of parotid gland massage performed to determine suppuration of parotid gland on amylase levels.